Model Rute Perjalanan Minimal Dengan Menggunakan Vehicle Routing Problem Pada PT X - Eko Sulistyono Sulistyono (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
In this research discusses the problem of distributing goods from a depot to several customer locations to minimize travel costs. The problem is solved by using the Vehicle Routing Problem method. The data used in this research is secondary data with 10 customers and one depot. The aim of this research is to form a model from the data that has been obtained and determine the optimal travel route based on the model that has been formed. The first step is to form the objective function of the problem, then form the constraints that may occur. After the model is formed, a solution to the problem is sought. The total cost of the trip is obtained by multiplying the cost of the trip per kilometer by the total distance traveled.